2020
DOI: 10.1038/s41598-020-60164-6
|View full text |Cite
|
Sign up to set email alerts
|

Macronutrient in soils and wheat from long-term agroexperiments reflects variations in residue and fertilizer inputs

Abstract: Previous studies in the long-term experiments at Pendleton, OR (USA), were focused on organic matter cycling, but the consequences of land management for nutrient status over time have received little attention. Soil and wheat (Triticum aestivum L.) tissue samples were analyzed to determine the macronutrient dynamics associated with residue management methods and fertilizer rate under a dryland winter wheat-fallow rotation. The treatments included: no burn residue incorporation with farmyard manure (FYM) or pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 40 publications
1
19
0
Order By: Relevance
“…Both management factors, analysed separately to avoid a non-homoscedastic additive model, also affected grain protein content (Table 5). Higher grain protein content and grain N harvest were recorded on crops where organic fertilisation was applied than on crops where it was not, in line with findings by Shiwakoti et al (2020) and Olesen et al (2009), although these latter authors also found a significant yield increase with the use of manure in organic wheat. Pedersen et al (2012) also found that farmyard manure is a significant source of N in organic wheat but its effect interacts with soil properties and past management.…”
Section: Effects Of Management Strategiessupporting
confidence: 84%
“…Both management factors, analysed separately to avoid a non-homoscedastic additive model, also affected grain protein content (Table 5). Higher grain protein content and grain N harvest were recorded on crops where organic fertilisation was applied than on crops where it was not, in line with findings by Shiwakoti et al (2020) and Olesen et al (2009), although these latter authors also found a significant yield increase with the use of manure in organic wheat. Pedersen et al (2012) also found that farmyard manure is a significant source of N in organic wheat but its effect interacts with soil properties and past management.…”
Section: Effects Of Management Strategiessupporting
confidence: 84%
“…Under different fertilizer and tillage treatments, Shiwakoti et al (2019a) found no differences in wheat grain mineral concentration except for manganese (Mn), which increased linearly with nitrogen (N) fertilizer rates. A different yet similar study demonstrated positive correlations between wheat grain Mn concentration and N fertilization, and greater N and Zn concentrations in wheat grain when fertilized with either farmyard manure or inorganic N (Shiwakoti et al, 2019b;Shiwakoti et al, 2020). Shiwakoti et al (2020) also reported an increase in N and S concentrations in wheat grain over time, speculating this could be due to greater N concentration in wheat grain occurring in cases where less rainfall occurred during the growing season.…”
Section: Crop Sciencementioning
confidence: 81%
“…(2019a) found no differences in wheat grain mineral concentration except for manganese (Mn), which increased linearly with nitrogen (N) fertilizer rates. A different yet similar study demonstrated positive correlations between wheat grain Mn concentration and N fertilization, and greater N and Zn concentrations in wheat grain when fertilized with either farmyard manure or inorganic N (Shiwakoti et al., 2019b; Shiwakoti et al., 2020). Shiwakoti et al.…”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation
“…Active C, as the substrate for microbial activity, is associated with a range of soil health benefits including nutrient cycling, production of organic binding agents, and aggregate formation and stability (Bronick & Lal, 2005;Haynes & Beare, 1996;Tejada & Gonzalez, 2003;Tisdall & Oades, 1982). Cox et al (2001), Reeve et al (2012), Tautges et al (2016), Calderón et al (2018), and Shiwakoti et al (2020 also showed benefits of compost/manure application to a range of dryland soil properties including soil organic C, macronutrients, and enzyme activities. These findings are also consistent with research conducted in more humid regions (Flieβbach & Mäder, 2000;Peacock et al, 2001).…”
Section: Discussionmentioning
confidence: 99%